2017
DOI: 10.1111/all.13204
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus in cystic fibrosis: An update on immune interactions and molecular diagnostics in allergic bronchopulmonary aspergillosis

Abstract: A wide spectrum of pathological conditions may result from the interaction of Aspergillus fumigatus and the immune system of its human host. Allergic bronchopulmonary aspergillosis is one of the most severe A. fumigatus-related diseases due to possible evolution toward pleuropulmonary fibrosis and respiratory failure. Allergic bronchopulmonary aspergillosis occurs almost exclusively in cystic fibrosis or asth- | ASPERGILLUS FUMIGATUS AND ITS INTERACTION WITH THE HUMAN HOSTThe Aspergillus genus comprises 339 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 98 publications
(214 reference statements)
1
36
0
2
Order By: Relevance
“…The important pre‐disposing to ABPA factor is the presence of fungi within the airways of the patients with asthma or cystic fibrosis (CF) 8‐10 . A fumigatus conidia are recognised via Toll‐like receptors on dendritic cells and airway epithelial cells, leading to production of TSLP, IL‐33, IL‐25 10,11 . Pivotal role of allergic inflammation is associated with TSLP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The important pre‐disposing to ABPA factor is the presence of fungi within the airways of the patients with asthma or cystic fibrosis (CF) 8‐10 . A fumigatus conidia are recognised via Toll‐like receptors on dendritic cells and airway epithelial cells, leading to production of TSLP, IL‐33, IL‐25 10,11 . Pivotal role of allergic inflammation is associated with TSLP.…”
Section: Introductionmentioning
confidence: 99%
“…Proteases secreted by A fumigatus activate proteinase‐activated receptors (PARs) and enhance secretion of IL‐8 in airway epithelial cells 10 . Gibsonat et al 18 found that the neutrophil chemoattractant, IL‐8, was elevated in ABPA, and therefore suggested that IL‐8 promotes neutrophil influx and activation.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] ABPA is associated with early allergic and late-phase inflammatory responses of the lungs to A. fumigatus antigens that occur in a minority (less than 1%) of patients with asthma and, more often (7%-10%), in patients with cystic fibrosis. [43] ABPA ways. [44][45][46] Proteases released from MCs can promote the release of growth factors from airway epithelial cells driving strong and irreversible remodelling reactions in airways of patients with ABPA, resulting in bronchiectasis lesions and fibrosis.…”
Section: C S Contribute To the Morb Id It Y Of A Sperg Illus Fumimentioning
confidence: 99%
“…1,2 Allergic bronchopulmonary aspergillosis (ABPA) is a severe ARD, with an estimated prevalence of 2.5% among asthmatic patients and up to 15% among patients with CF. 3 The detection of Af-specific IgE (Af-IgE) through serological or skin tests defines Af sensitization, a common finding in patients with asthma or CF. 2,4,5 A "raised" level of Af-IgE is a major ABPA diagnostic criterion, 6 but the definition of "raised" IgE is still lacking.…”
Section: A New Ige Western Blot Identifies Aspergillus Fumigatus Sensmentioning
confidence: 99%
“…2,3 However, discerning ABPA-related "raised" IgE from non-ABPA Af sensitization is crucial for ABPA identification, staging, and treatment choice aiming at preventing lung function deterioration. 2,3,7 Molecular allergen profiling brought more accurate IgE analysis, 7,8 but only 5/23 characterized Af allergens are currently commercialized. 9 An alternative approach using western blot (WB) would enable one-step characterization of sensitization to a greater number of Af molecules.…”
Section: A New Ige Western Blot Identifies Aspergillus Fumigatus Sensmentioning
confidence: 99%